Age of Rotational Landslides in the Cypress Hills, Alberta-Saskatchewan - Goulden, Mark; Sauchyn, David (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTThe topography of the west block of the Cypress Hills indicates that fluvial dissection of the plateaux and subsequent rotational landsliding of valley sides have been the dominant Quaternary geomorphic processes. This paper presents a preliminary chronology of rotational landslides based on the relative ages of 17 landslides and on 3 absolute dates. Four indices of relative age were used: organic content in Ah and B soil horizons, the size and coverage of lichens and weathering rind thickness on boulders exposed by landsliding, and the concavity and gradient of gullies in landslide debris, One landslide occurred in 1965. Organic materials collected from buried soil horizons beneath depressions on 3 other landslides were radiocarbon dated at 1235 ± 105, 1635 ± 105 and 7259 ± 165 yrs. BP. Microscopic analysis of the organic material revealed that the oldest sample was contaminated with older carbon. Cluster analysis of the relative age data in conjunction with 3 acceptable absolute dates suggests that the landslides under study have occurred during late Holocene time.